2015
DOI: 10.1038/modpathol.2014.95
|View full text |Cite
|
Sign up to set email alerts
|

B-cell lymphomas with concurrent MYC and BCL2 abnormalities other than translocations behave similarly to MYC/BCL2 double-hit lymphomas

Abstract: Large B-cell lymphomas with IGH@BCL2 and MYC rearrangement, known as double-hit lymphoma (DHL), are clinically aggressive neoplasms with a poor prognosis. Some large B-cell lymphomas have concurrent abnormalities of MYC and BCL2 other than coexistent translocations. Little is known about patients with these lymphomas designated here as atypical DHL. We studied 40 patients of atypical DHL including 21 men and 19 women, with a median age of 60 years. Nine (23%) patients had a history of B-cell non-Hodgkin lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 37 publications
5
64
0
1
Order By: Relevance
“…Furthermore, genomic and gene expression profiling have landscaped DLBCLs in adults as a heterogenous entity, while in children, they are predominantly homogenous, with a germinal centre immunophenotype and a lack of t (14;18). HGBL, with MYC and BCL2 or BCL6 rearrangements are reported rarely in young adults, adolescents and children [3][4][5]. Two children, aged 9 and 11 years, with HGBL with MYC/BCL6 aberrations are documented but HGBL with MYC and BCL2 translocations, are unreported in children, to date [5,[14][15][16][17].…”
Section: • Dual Expression But Not Dual Rearrangements Of Myc and Bcl2mentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, genomic and gene expression profiling have landscaped DLBCLs in adults as a heterogenous entity, while in children, they are predominantly homogenous, with a germinal centre immunophenotype and a lack of t (14;18). HGBL, with MYC and BCL2 or BCL6 rearrangements are reported rarely in young adults, adolescents and children [3][4][5]. Two children, aged 9 and 11 years, with HGBL with MYC/BCL6 aberrations are documented but HGBL with MYC and BCL2 translocations, are unreported in children, to date [5,[14][15][16][17].…”
Section: • Dual Expression But Not Dual Rearrangements Of Myc and Bcl2mentioning
confidence: 99%
“…The aggressive clinical course of DHL is typified by advanced disease stage with a high-intermediate or high International Prognostic Index, extranodal spread, including frequent bone marrow and CNS involvement and elevated serum lactate dehydrogenase levels [3,4,10]. Some studies have identified heightened gastrointestinal tract involvement [3,10,11].…”
Section: • Dual Expression But Not Dual Rearrangements Of Myc and Bcl2mentioning
confidence: 99%
See 2 more Smart Citations
“…88,113,114,117,[126][127][128] To further confound the issue of definition of DH, one study has suggested that so-called "atypical DH lymphomas" (those with single translocations of MYC or BCL2 with copy number alterations of the other gene, or copy number alterations of both genes) have similar poor outcome to conventional DH lymphomas. 87,129,130 In addition to potential clinical importance associated with MYC partner genes, there may be histologic associations as well. A non-IG partner gene was associated with DLBCL morphology.…”
Section: B-cell Lymphomamentioning
confidence: 99%